AKHLAK ANAK TERHADAP ORANG TUA (Studi Kitab Washoya Al Abaa Lil Abnaa Karya Syaikh Muhammad Syakir Al-Iskandari) - Faiq Ulul 'Azmi; Ngarifin Shidiq; Mukromin Mukromin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study explores the moral duties of children toward their parents as presented in Washoya al-Abaa lil-Abnaa by Shaykh Muhammad Syakir al-Iskandari, a classical Islamic text offering ethical guidance that remains relevant amid current moral decline among youth. Using a qualitative library-research approach, the researchers analyzed the primary text along with supporting literature to identify its core moral teachings. The findings highlight several key principles: speaking respectfully and gently, recognizing parents’ sacrifices, and obeying parental guidance in line with Islamic values. Practical applications include maintaining proper manners, helping parents in daily life, and praying for them during their lifetime and afterward. These teachings continue to hold contemporary significance, serving as a moral foundation that can strengthen family bonds and support the integration of Islamic character education in today’s learning contexts.